Release of antidiabetic peptides from Stichopus japonicas by simulated gastrointestinal digestion. (15th June 2020) - Gong, Pi-Xian; Wang, Bing-Kun; Wu, Yan-Chao; Li, Qin-Ying; Qin, Bang-Wei; Li, Hui-Jing
Graphical abstract: Highlights: Peptides were released from sea cucumber by in vitro gastrointestinal digestion. Peptides obtained were predicted to be potential inhibitory of DPP-IV. Antidiabetic activity was detected in 3T3-L1 cells and Hep G2 cells. In silico results indicated that peptides inhibit DPP-IV like anagliptin. Abstract: Sea cucumber ( Stichopus japonicus ) is a high-protein food with the potential to release certain peptides through enzymolysis. This work is to explore the characteristics of peptides released from Stichopus japonicus protein in the process of digestion. Hydrolysates were obtained by gastrointestinal digestion and fractioned to <3, 3–10, 10–30 and >30 kDa fractions. Fifty-eight peptides from <3 kDa fraction were characterized using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Hydrolysates could improve glucose uptake of 3 T3-L1 cells and high insulin-induced insulin-resistant Hep G2 cells. Molecular docking showed that the released peptides had similar binding mode with anagliptin, a dipeptidyl peptidase IV (DPP-IV) inhibitor. The <3 kDa fraction in gastro and intestinal digestion showed the greatest DPP-IV inhibitory potency (IC50 0.51 and 0.52 mg/mL, respectively). The results indicated that sea cucumber could be used as a functional food to release antidiabetic peptides through gastrointestinal digestion.